Battery electric vehicles – implications for the driver interface. Issue 3 (3rd March 2016) - Neumann, Isabel; Krems, Josef F.
Abstract: The current study examines the human–machine interface of a battery electric vehicle (BEV) from a user-perspective, focussing on the evaluation of BEV-specific displays, the relevance of provided information and challenges for drivers due to the concept of electricity in a road vehicle. A sample of 40 users drove a BEV for 6 months. Data were gathered at three points of data collection. Participants perceived the BEV-specific displays as only moderately reliable and helpful for estimating the displayed parameters. This was even less the case after driving the BEV for 3 months. A taxonomy of user requirements was compiled revealing the need for improved and additional information, especially regarding energy consumption and efficiency. Drivers had difficulty understanding electrical units and the energy consumption of the BEV. On the background of general principles for display design, results provide implications how to display relevant information and how to facilitate drivers' understanding of energy consumption in BEVs. Practitioner Summary: Battery electric vehicle (BEV) displays need to incorporate new information. A taxonomy of user requirements was compiled revealing the need for improved and additional information in the BEV interface. Furthermore, drivers had trouble understanding electrical units and energy consumption; therefore, appropriate assistance is required. Design principles which are specifically important in the BEV context are discussed.